Sports Sustainability in Romania. How Sports Clubs in Romania's Football 1st Division Communicate about Sustainability - Constantin-Daniel PESTREA; Mihaela CONSTANTINESCU; Ana-Ruxandra-Cornelia NEACȘU; Florina BOTEZATU (Journal of Emerging Trends in Marketing and Management, 2025)
This paper aims to highlight the level of knowledge and applicability of sustainability in sport at the level of sports entities in Romania. The importance of sustainability in sport is becoming increasingly evident worldwide, as major sporting events are among the largest generators of CO2 emissions, considering that the last 4 editions of the Olympic Games have averaged more than 2 million tons of CO2 emissions during the Games. In order to find out how this phenomenon is reflected in Romania, we conducted a direct, observational-based research, analyzing the communication policy of sports entities on the main online channels (social media and websites). This research was realized in the field of football, the main trend-setting sport in Romania. In the specialized literature, sustainability is, most often, measured in terms of its three dimensions: the economic, the social and the environmental dimension. , which is the structure that has been used also for the analysis of sports organizations’ online communication from the present study.The main research results indicate that there is a stand-alone strategy dedicated to sustainability both at the highest level of football in Romania (the Romanian Football Federation), and for some of the sports clubs registered in the Romanian football 1st Division. However, there are still some clubs that have their sustainability approach included in their overall strategy. Another relevant result shows that most of the sustainability actions communicated by Romanian football clubs are limited to the social dimension. This work can be useful for all Romanian sport federations and clubs, the National Agency for Sport (the equivalent of the sports ministry), the Romanian Olympic and Sport Committee, NGOs, athletes and people involved in sport, in the process of raising awareness of the importance of an effective strategy dedicated to sustainability.